A trivalent gC2/gD2/gE2 vaccine for herpes simplex virus generates antibody responses that block immune evasion domains on gC2 better than natural infection. Issue 4 (21st January 2019) - Hook, Lauren M.; Awasthi, Sita; Dubin, Jonathan; Flechtner, Jessica; Long, Deborah; Friedman, Harvey M.
Highlights: Our goal is to produce antibodies to immune evasion domains through immunization. Antibodies produced by HSV infection bind gC2 yet do not block gC2 binding to C3b. Antibodies produced by immunization bind gC2 and prevent C3b from binding. Immunizing infected animals produces gC2 antibodies that prevent C3b from binding. Vaccines make the weakly immunogenic immune evasion domains of gC2 more immunogenic. Abstract: Vaccines for prevention and treatment of genital herpes are high public health priorities. Our approach towards vaccine development is to focus on blocking virus entry mediated by herpes simplex virus type 2 (HSV-2) glycoprotein D (gD2) and to prevent the virus from evading complement and antibody attack by blocking the immune evasion domains on HSV-2 glycoproteins C (gC2) and E (gE2), respectively. HSV-2 gC2 and gE2 are expressed on the virion envelope and infected cell surface where they are potential targets of antibodies that bind and block their immune evasion activities. We demonstrate that antibodies produced during natural infection in humans or intravaginal inoculation in guinea pigs bind to gC2 but generally fail to block the immune evasion domains on this glycoprotein. In contrast, immunization of naïve or previously HSV-2-infected guinea pigs with gC2 subunit antigen administered with CpG and alum as adjuvants produces antibodies that block domains involved in immune evasion. These results indicate that immune evasion domains on gC2 are weak antigens during infection, yet when used as vaccine immunogens with adjuvants the antigens produce antibodies that block immune evasion domains.